Application of allograft and absorbable screws in the reconstruction of a massive bone defect following resection of giant osteochondroma: A retrospective study - Ma, Zhihao; Yang, Qiang; Liu, Xinyu; Li, Zhenfeng (Frontiers in Surgery, 2022)
Background This study aims to introduce a reconstruction method of applying allografts and absorbable screws to repair large bone defects caused by the resection of giant osteochondroma. Methods A retrospective study of a series of patients who underwent the resection of giant osteochondroma reconstructed by allografts and absorbable screws was conducted from February 2020 to September 2021. Their demographic data, location site, area of bone defect, and pertinent operative details were recorded. The reconstruction modality of allografts was elaborated on. In the follow-up, radiographic images were utilized to determine bone union, and the Musculoskeletal Tumor Society score was used to evaluate postoperative limb function. Results A total of seven patients were included, including three males and four females with an average age of 16.6 ± 6.5 years. Among them, three cases of tumors occurred in the humerus and four cases occurred in the femur. The average follow-up time was 11.3 ± 3.0 months. The average area of bone defect was 25.9 ± 8.3 cm2. No complications such as infection, nonunion, and allograft bone fracture were found during the follow-up period. Six months after the operation, the average Musculoskeletal Tumor Society score was 26.4 ± 1.6, with acceptable postoperative function. Conclusions The cooperative application of absorbable screw fixation and allografts including mixed cortical bone and cancellous bone, which yielded satisfactory functional outcomes and acceptable postoperative complications, is an effective reconstruction method for a massive bone defect after the resection of giant osteochondroma.